Biomarkers and personalised medicine in rheumatoid arthritis: a proposal for interactions between academia, industry and regulatory bodies. Issue 10 (22nd July 2011) - Miossec, P; Verweij, C L; Klareskog, L; Pitzalis, C; Barton, A; Lekkerkerker, F; Reiter, S; Laslop, A; Breedveld, F; Abadie, E; Flamion, B; Dere, W; et al.
Abstract : Rheumatoid arthritis (RA) is one of the most appropriate conditions for the application of personalised medicine as a high degree of heterogeneity has been recognised, which remains to be explained. Such heterogeneity is also reflected in the large number of treatment targets and options. A growing number of biologics as well as small molecules are already in use and there are promising new drugs in development. In order to make the best use of treatment options, both targeted and non-targeted biomarkers have to be identified and validated. To this aim, new rules are needed for the interaction between academia and industry under regulatory control. Setting up multi-centre biosample collections with clear definition of access, organising early, possibly non-committing discussions with regulatory authorities, and defining a clear route for the validation, qualification and registration of the biomarker–drug combination are some of the more critical areas where effective collaboration between the drug industry, academia and regulators is needed.